Local knowledge on Moroccan Siroua sheep management assists its resilience to climate change - Ibnelbachyr M.; Benjelloun B.; El Amiri B. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Indigenous livestock genetic resources play a significant role in promoting biodiversity and improving ecosystem resilience to climate change in their area. In Center-eastern Morocco, Siroua sheep is a good example of adaptation to harsh environments in high altitudes (1800 m to more than 3000 m) where rainfall is very low and irregular (115 to 260 mm/year) and temperatures vary from –5 to +20 °C in winter and from +30 to +45 °C during summer. The aim of this study was to explore how herders and shepherds manage the Siroua sheep to mitigate climate change impacts. Based on the results of a prospective study and a field survey, sheep feeding is based mainly on rough grazing lands through transhumance between high mountain pastures in summer and lowlands in winter. Thus, the local knowledge on management makes the breed resilient to many drought conditions occurring in Siroua geographical area. Sheep graze a variety of shrubs and herbaceous plants at the rough grazing lands. Additionally, animals are supplemented with cereal grains and straw in case of severe drought or snow. These local practices should be accompanied by a conservation and breeding program to prevent extinction of this indigenous sheep in the future.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)